Effects of Superabsorbent Polymers on Infiltration and Evaporation of Soil Moisture Under Point Source Drip Irrigation1. (12th January 2015) - Yang, Linlin; Han, Yuguo; Yang, Peiling; Wang, Chengzhi; Yang, Shengmin; Kuang, Shuya; Yuan, Hanzheng; Xiao, Congying
Abstract The application of superabsorbent polymers (SAPs) in agriculture can enhance water use efficiency and ease water shortage in agriculture. In this study, by applying SAPs to the middle layer of the soil root zone, the effects of SAPs on moisture distribution during infiltration and evaporation under the condition of point source irrigation were investigated. The results show that during infiltration, the wetting front formed an accident change zone in the horizontal direction; in the bottom layer, the horizontal infiltration rate is greater than the vertical infiltration rate due to the effect of SAPs from the middle layer; the soil water content in the middle layer increased remarkably by 23.6%, higher than that in the surface and bottom layers; during evaporation, the soil water content changed significantly in the surface layer due to strong evaporation on the surface, it was largest and quite even in the SAP–soil mixture layer, and decreased the least in the bottom layer due to water storage in the mixture layer. Therefore, SAP application in the crop root layer is helpful to conserve soil water content in the crop root zone, inhibit evaporation of soil water in the lower layer and facilitate moisture conservation. Copyright © 2015 John Wiley & Sons, Ltd.